Identification of a novel frameshift variation in ANKRD11: a case report of KBG syndrome - Shao, Qing; Jiang, Qiang; Luo, Yuqi; Meng, Yimei; Tian, Guoyu; Yin, Xiao (Frontiers in Genetics, 2025)
BackgroundKBG syndrome (KBGS, OMIM: 148050) is a rare genetic disorder characterized by macrodontia, short stature, skeletal abnormalities, and neurological manifestations. The objective of this study is to investigate a case of KBG syndrome caused by a novel frameshift mutation in ANKRD11.Methods and resultsWe present the case of an 18-year-old Chinese male exhibiting characteristic features including a triangular face, micrognathia, hypertelorism, macrodontia, bushy eyebrows, prominent ears, short stature, low hairline, delayed cognitive development, and scoliosis. Whole exome sequencing identified a novel frameshift variant in the ANKRD11 gene which ultimately led to the diagnosis of KBG syndrome.ConclusionIn this study we have identified a previously unreported frameshift variant (NM_013275.6:c.2589dup) in ANKRD11 that causes KBG syndrome. This finding expands both the molecular and clinical spectrum of this rare genetic disease.